Biodiversity and Relationships in Species Annonaceae Using the Phenetic Method in the Purwodadi Botanical Garden - Hamidah; Junairiah; Putri Akustia (Postgraduate, University of Mataram, 2025)
This study aims to analyze the morphological diversity and phylogenetic relationships of six species from the Annonaceae family at the Purwodadi Botanical Garden using a phenetic approach. The background of this research is based on the importance of character-based identification to support taxonomy, conservation, and plant classification within the Annonaceae family, which is known for its high diversity. The research began with field exploration and specimen identification, followed by morphological characterization focusing on stem, leaf, petiole, and flower traits. Data acquisition was conducted by direct observation and measurement using tools such as calipers, rulers, and color tables. The morphological data were analyzed using Hierarchical Cluster Analysis and Principal Component Analysis (PCA) with SPSS 25.00 software to determine phylogenetic relationships among the species. The results revealed two major clusters: the first includes Mitrephora polyprena, Stelechocarpus burahol, Orophea enneandra, and Polyalthia bullata, with a similarity index of 73.2%, and the second consists of Annona muricata and Miliusa horsfieldii, with 59.3% similarity. PCA results indicated that leaf width, leaf length, petiole length, leaf color, and stem surface were the most influential morphological traits. These findings demonstrate that the phenetic approach is effective for analyzing phylogenetic relationships and can contribute to conservation strategies and biodiversity management.